Analysis of the products resulting from the electrocatalytic oxidation of ethylene on Ru / Pt electrodes - Colina, José; Choy, Marisela; Martínez, Hugo (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> Electrolyses of solutions of phosphoric acid 0,5 M saturated with ethylene was carried out by means of the application of potentials programmed to underpotentially deposited monolayer of Ru on a Pt electrodes (upd). The covered (q) of Ru (upd) at Pt was 0,5. Chromatographic analysis of the electrolytic solutions show as majority product the CO2 (58,15%), and other products like CH3CH2OH (13,84%), CH3COOH (19,41%), CH3OH (4,63%), in smaller proportion HCHO, CH3COCH3, HCOOH and non identified appearances. A program of three steps was used as electrochemical method and the results show that the applied potentials and the covered of the adátomos of Ru were decisive for the selectivity of the products obtained to temperature of 22°C and ambient pressure.Â